Childhood Idiopathic Nephrotic Syndrome: Does the Initial Steroid Treatment Modify the Outcome? A Multicentre, Prospective Cohort Study - Pasini, Andrea; Bertulli, Cristina; Casadio, Luca; Corrado, Ciro; Edefonti, Alberto; Ghiggeri, GianMarco; Ghio, Luciana; Giordano, Mario; La Scola, Claudio; Malaventura, Cristina; Maringhini, Silvio; Mastrangelo, Antonio P.; et al. (Frontiers in Pediatrics, 2021)
BACKGROUND: a great majority of children with idiopathic nephrotic syndrome will relapse after successful treatment of the initial episode. The possibility that different steroid dosing regimens at onset, adjusted for risk factors, can reduce the rate of relapse represents an interesting option to investigate. OBJECTIVES: to evaluate the effect of the initial steroid regimen, adjusted for time to remission (TTR), on the frequency of relapses and steroid dependence, and to verify the influence of prognostic factors on disease course. METHODS: a multicentre, prospective, cohort study. Children with nephrotic syndrome, with TTR ≤10 days (Group A), were given a 20-week prednisone regimen (2828 mg/m2) and those with a TTR >10 days, a 22-week regimen (3668 mg/m2) (Group B). Previously published retrospective data from the same centres were also evaluated. Main outcomes were: relapse rate, number of frequent relapsers + steroid dependent children and total prednisone dose after induction. RESULTS: 143 children were enrolled. Rate of relapsed subjects (77% vs. 79%) and frequent relapsers + steroid dependent subjects (40% vs. 53%) did not differ between Groups A and B, or between the retrospective and prospective cohorts. The cumulative prednisone dose taken after the induction treatment was similar in both groups and in the retrospective and prospective cohorts. TTR was not associated with relapse risk. Age at onset and total serum protein were significantly lower in relapsing patients. At ROC analysis, the best cut-off was 5.3 years for age at onset and 4.2 g/dL for total serum protein. According to these cut-offs, older children with higher total serum protein had a higher relapse free survival rate (58%) than younger children with lower total serum protein (17%). CONCLUSIONS: TTR was not found to be a prognostic factor of relapse; because of this, different steroid regimens, adjusted for TTR, did not modify the relapse rate in any relevant measure. Conversely, younger age and low total serum protein were independent predictors of relapse risk, however this outcome was not modified by higher prednisone regimens.